Country Partnership Framework for Romania for the Period FY19-23 - World Bank Group (World Bank, Washington, DC, 2018)
Romania has achieved impressive successes, yet it continues to face formidable challenges. This growing divide is, in effect, producing two very different Romanias. Significant risks of climate and natural disaster events threaten the country’s economic resilience, and require urgent policy reform and infrastructure investment. The recently completed Systematic Country Diagnostic (SCD) identifies the most critical constraints to sustainable economic growth and shared prosperity. This has limited the Government’s ability to implement important public policies to boost the economy’s growth potential, build key economic infrastructure, create equal opportunities and jobs for all citizens, and improve resilience to natural disasters. Shortcomings in public service delivery, especially to the poor, are often caused by large under performing State-Owned Enterprises (SOEs), but also by inefficient policies and low administrative capacity. The World Bank Group (WBG) is uniquely positioned to support Romania by helping to strengthen its institutions and accelerate the country’s convergence with more advanced EU states. Strengthening institutions for improved service delivery and creating or deepening markets for the private sector are areas where the WBG has comparative advantage, playing a selective, catalytic and innovative role. Future WBG activities would have to show that they build essential institutional capacity and/or bring clear IFC additionality. WBG financing would be assessed using the following three additional filters: (i) developing innovative solutions that benefit the most poor and vulnerable, including Roma; (ii) maximizing finance for development, including catalyzing private sector investment or leveraging additional resources (e.g., better absorption of EU funds); and/or (iii) contributing to regional and global public goods. In other words, WBG will support investment, advisory or knowledge operations in Romania that help build institutions and markets for sustainable and broad-base growth, and share global knowledge. The FY19-23 CPF proposes a selective program that addresses the main constraints identified in the SCD. The planned WBG program will focus on all priority areas identified in the SCD, with the first, building institutions, serving as the prerequisite for advancing on the other three: (i) ensure equal opportunities for all; (ii) catalyze private sector growth and competitiveness; and (iii) build resilience to shocks. The proposed CPF is more focused than previous ones, drawing on the lessons learned to fit the specific policy environment of Romania. First, set modest objectives: past projects targeting complex and ambitious reforms did not adequately factor in issues related to political and legislative volatility and weak capacity. Second, leverage all instruments : successes were achieved using a mix of instruments—lending and advisory—for impact. Third, support the implementation of strategies for real institutional change: a greater emphasis on hands-on implementation support embedded in investment operations is an effective complement to ongoing capacity building efforts through a broad RAS program.